Beyond periodicity: tailoring Tamm resonances in plasmonic nanohole arrays for multimodal lasing - Shadman Shahid; Muhammad Anisuzzaman Talukder (New Journal of Physics)
Extraordinary optical transmission (EOT) through metal nanohole arrays (NHAs) and Tamm plasmon (TP) states have been investigated in plasmonic devices since 1998 and 2007, respectively. Since their introduction, various potential applications for structures that support these phenomena have been reported, including plasmonic absorbers, lasing cavities, and narrowband filters. The performance of EOT- and TP-based devices is significantly influenced by the sizes and patterns of the holes in the NHA. While the effects of hole size and shape on EOT have been extensively studied, similar research on TP structures involving metal NHAs is still lacking. Particularly, the impact of gradually introducing randomness into the metal NHA on TP modes has yet to be explored. In this work, we modify the hole sizes and arrangements of the metal NHA and examine the effects on EOT and Tamm resonances. We investigate three scenarios: the bare metal NHA, a passive Tamm resonant cavity, and a TP laser. We observe that multiple Tamm resonances appear as the periodicity of the holes increases. However, these resonances vanish when the hole arrangement shifts from a regular array to a pseudo-periodic random array, which is defined as a collection of holes placed randomly within a periodically repeating square unit cell. These multiple resonances can be attributed to the folding of dispersion lines in a periodically patterned TP cavity. The dispersion characteristics of the NHA array-based structures are calculated and analyzed to understand better the multiple resonances in the transmission and lasing emission patterns.